Does Image Grid Visualization Affect Password Strength and Creation Time in Graphical Authentication? - Katsini, Christina; Raptis, George E.; Fidas, Christos; Avouris, Nikolaos (Proceedings of the 2018 International Conference on Advanced Visual Interfaces, 2018)
Nowadays, technological advances introduce new visualization and user interaction possibilities. Focusing on the user authentication domain, graphical passwords are considered a better fit for interaction environments which lack a physical keyboard. Nonetheless, the current graphical user authentication schemes are deployed in conventional layouts, which introduce security vulnerabilities associated with the strength of the user selected passwords. Aiming to investigate the effectiveness of advanced visualization layouts in selecting stronger passwords, this paper reports a between-subject study, comparing two different design layouts a two-dimensional and a three dimensional. Results provide evidence that advanced visualization techniques provide a more suitable framework for deploying graphical user authentication schemes and underpin the need for considering such techniques for providing assistive and/or adaptive mechanisms to users aiming to assist them to create stronger graphical passwords.
Keywords: graphical password strength; graphical passwords; image grid; recognition-based graphical authentication; usable security